TINGKAT PARTISIPASI ANGKATAN KERJA MASYARAKAT MISKIN DI RT.01 RW.06 DESA TEGAL GEDE KECAMATAN SUMBERSARI KABUPATEN JEMBER - Moh. Taufiq Fudloli; Sukidin Sukidin (Economic Education, University of Jember, 2015)
Working age population is the population age 15-64 years old, consisting labor force and non-labor force. The labor force includes people who have jobs, unemployed, and also those who are still searching for jobs, while non-labor force includes those who focus on attending scholl and taking care of the household matter. The more people who work will lead to a larger number of labor force, which then will result in a high rate of labor force participation. This happens to the poor people in Tegal Gede RW.06 RT.01 Sumbersari Jember. Purposive area method was employed to the termine the research location. While population method was used to define the respondents of 83 members of labor force. Interviews, questionnaires and documentation were employed to collect the data. Data analysis used in this study is a descriptive analysis. The results show that the working age population of 123 people, consisting of 83 persons of labor force and 40 persons of non-labor force. The large number of labor force available has resulted in a high labor force participation rate of the poor people in RW.06 RT.01 Tegal Gede Sumbersari Jember at 68%, which on the other hand they still have low income. The high level labor force participation in the village shows that people working age prefer to work from school and take care of household although the level of wages that they receive low.